Determining the level of knowledge and consumption of probiotics and prebiotics among athletes in Jordan - Ola D. Al-Maseimi; Leena Ahmad; Nour A. Elsahoryi; Lena Al-Maaitah (Journal of Nutritional Science)
Interest in probiotics and prebiotics in sports nutrition is growing, but research on Jordanian athletes remains limited. While gut microbiota influences athletic performance, little is known about athletes’ understanding and use of probiotic- and prebiotic-rich foods in this region. This exploratory study investigates the knowledge, dietary habits, and correlations with gastrointestinal (GI) problems among Jordanian athletes to inform future research and interventions. The study provides insights into how awareness and consumption of gut-supportive foods can impact GI health, offering broader nutritional implications for global dietary strategies for athletes. A standardised questionnaire was administered to 324 athletes (ages 18–22) to assess knowledge, dietary practices, and GI symptoms. Descriptive statistics summarised the data, and chi-square tests examined associations among knowledge, diet, and GI symptoms (p < 0.05). Knowledge and diet were scored based on correct responses and reported intake of gut-supporting foods. Results showed that 55.9% of athletes were familiar with probiotics and 32.1% with prebiotics. The majority reported low consumption of probiotic- and prebiotic-rich foods, with 72.2% scoring low on diet intake. Although 60.5% seldom consumed fast food, overall intake of gut-supportive foods was limited. No statistically significant associations were found, but a weak positive trend between dietary habits and GI symptoms was observed, suggesting diet may have a modest influence on GI health. Living arrangements influenced both dietary choices and GI symptoms. This study highlights the need for targeted nutrition education to improve awareness and intake of probiotics and prebiotics, potentially supporting GI health and enhancing athletic performance.